"The Eagle and the Coins. Allegorical agency in images by Gary Hill" - Conde, I. (Fifth International Conference On The Image, Berlin, 29-30 October 2014, 2014)
This conference is about the image's agency. “Images can be willed”, it is said, “what’s in the imagination for now can become an agenda for practice and politics tomorrow”. Based in a iconological approach, my purpose is to see agency in allegory in two media installations by Gary Hill: Frustrum and Guilt (2006-2007). Renowned for his “electronic linguistics”, Gary Hill takes a conceptual and radical approach to the media quite opposite to documentary video. Or uses of it as in "cinematic" and political trends in contemporary art since the 90's. Yet those installations seemed to have semantics that questioned the notion of value, money, power and decadence. In Frustrum, a computer-generated eagle was trapped within a pyramidal shaped electrical pylon while on the floor was a pool of black oil with a floating brick of pure gold, accompanied by the sentence: “for everything which is visible is a copy of that which is hidden.” Guilt showed five gold coins on motorized pedestals depicting the artist’s face being punched, accompanied by Latin phrases about guilt. A possible allegory of the decline of the Roman Empire. The self-infliction was crowned by a laurel branch and the statement “Ars est corpus vile: Art is a worthless body”. Maybe not. Art acts by its shrewd and critical agency to oversee and reframe our world, even if only in the imaginary and utopia.